Efektivitas Program Selaras Ecosystem di Kampung Cicayur Desa Pagedangan Kecamatan Pagedangan Kabupaten Tangerang - Tami Masfufah; Kandung Sapto Nugroho (INDO PUBLISHING, 2026)
The Selaras Ecosystem Waste Bank Program is a community-based initiative that promotes sustainable waste management and environmental awareness. This study aims to evaluate the effectiveness of the program in Kampung Cicayur, Pagedangan Village, Tangerang Regency. A quantitative descriptive method was employed using questionnaires distributed to 98 program members. Data were analyzed based on Campbell's program effectiveness theory, covering Program Success, Target Achievement, Program Satisfaction, Input and Output Levels, and Overall Goal Achievement. The program achieved an actual score of 9,832 out of an ideal score of 11,760 (83.61%), indicating an effective category. Program Satisfaction recorded the highest percentage (86.31%), while Target Achievement showed the lowest (79.59%). Overall, the program effectively achieved its objectives and contributed to community-based sustainable waste management.